Investigation of Geotechnical Seismic Isolation Systems Based on Recycled Tire Rubber-Sand Mixtures - Saglam, Dogan; Tonaroglu, Murat (MDPI, 2025)
In geotechnical earthquake engineering, enhancing the seismic properties of foundation soil to modify the characteristics of earthquake waves transmitted to structures presents a viable solution. This study investigates the effect of placing an isolation layer, composed of a mixture of recycled tire rubber and sand, beneath structures to mitigate seismic forces acting on buildings situated on soil layers with high amplification potential. In other words, the role of a soil layer functioning as a seismic isolator is examined. To achieve this objective, the seismic behavior of building-type structures is analyzed through numerical simulations, supplemented by laboratory experiments available in the literature. The numerical analyses are performed in the frequency domain using the finite element method within a one-dimensional (1D) framework. To validate the feasibility of the proposed isolation layer based on parametric analysis results, comparisons are made with laboratory tests available. In the literature, seismic isolation applications with thicknesses ranging from 1 to 3 m resulted in reductions of 6.8% to 16.17% in response spectral accelerations measured at the surface, while improvements in Fourier amplitude ratios ranged between 12.03% and 13.98%. This approach aims to provide an economical and efficient solution for earthquake-resistant structures while simultaneously promoting sustainability by recycling waste tires, contributing both to environmental conservation and economic benefits.
Keywords: isolation; GSI (geotechnical seismic isolation); soil amplification; DeepSoil software; numerical analysis; recycling; DYNAMIC PROPERTIES; SOIL MIXTURES; BUILDINGS; Chemistry; Engineering; Materials Science; Physics